iCollect mobile application for e-portfolio: experiences from an instructional design perspective - Md Ghalib, Mohd. Feham; Sahrir, Muhammad Sabri; Mat Daud, Nuraihan; Hassan, Haslina; Mohin, Mohaida (USM Press, 2014)
The present study seeks to shed some light on a workable model of George’s rapid prototype (2000) for the use and development of a mobile application for learning through an e-portfolio. In particular, this application focuses on sharing various types of artifacts, reflective journal writing, and learning experiences between students and their peers in a more convenient way via mobile devices such as iPhones, iPads or android-based smart devices. This study explores the prototype development and implementation phases of mobile accessibility on an e-Portfolio service available to the institutional community. Initially, a needs analysis of the end-users was conducted to best determine the preferences and styles of interactivity that they might expect using mobile applications. Clearly, this consideration will provide the platform with added value for the students and the lecturer alike. The resulting platform will enrich the learning and teaching experiences, as well as realizing the true unleashed potential of communicating and sharing via the mobile approach. Given that the use of mobile devices for educational purposes is currently ubiquitous, the current effort illustrates best how such tools might be used to support teaching and learning processes (Thornton and Houser, 2004; Proctor and Burton, 2003; Colley and Stead 2003).